The representation of Christ in Habitó entre nosotros of José Watanabe: the tension between the human and the divine - Flores Alemán, Marco (2023)
This article is a product of a wider research about Christ’s representations in Latin-American poetry, specifically in the cases of Peru and Mexico. Being Latin America a Christianized region, it’s important to explore the relationships between poetry and gospel, the representations of the religious and its implications in the collective imaginaries. Art is a privileged space for the construction of these and for the interpretation of reality. In that context, this research is focused on the case of a paradigmatic poetry collection of Christ’s representations: José Watanabe’s Habitó entre nosotros (1945-2007). The goal was to discover in what ways is represented the Christian figure in its verses. In addition, a hermeneutic methodology allowed a reading, analysis and interpretation of every poem accompanied with their intertextual evangelical referents at all time. This involved a comparative dynamic between the facts as they are narrated in the gospels and their reconfiguration in the poems. This concludes that Habitó entre nosotros (2001) represents Jesus from the tension between his human and divine nature, giving greater weight to the first of them by means of a new configuration of the acts and words of Christ.